The effects of royal jelly on performance and fatty acid profiles of different tissues in quail (Coturnix coturnix japonica) reared under high stocking density - Seven, Ismail; Simsek, Ulku Gulcihan; Gokce, Zehra; Tatli Seven, Pinar; Arslan, Aslihan; Yilmaz, Okkes (Tubitak Scientific & Technological Research Council Turkey, 2014)
To study the effects of royal jelly (RJ) on performance and fatty acid profiles, 168 unsexed 8-day-old quails (Coturnix coturnix japonica) were assigned to 4 treatment groups. Groups were arranged as follows: control (LSD; 160 cm(2)/quail and no supplementation), high stocking density (HSD; 80 cm(2)/quail and no supplementation), HSD-RJ 250 [80 cm2/quail and 250 mg/kg body weight (BW) RJ given orally], and HSD-RJ 500 (80 cm(2)/quail and 500 mg/kg BW RJ given orally). Body weight gain decreased significantly in the HSD group at day 42 (P < 0.01). Feed intake (FI) and feed conversion rate (FCR) were also significantly affected in the HSD group (P < 0.01). FI and FCR were improved by both doses of RJ. Both RJ doses increased total polyunsaturated fatty acid ratios in the breast, kidney (P < 0.001), leg, and liver (P < 0.05). Total saturated fatty acid ratios in leg (P < 0.01) and kidney (P < 0.05) tissues increased in the HSD group but decreased in the livers of HSD-RJ 250 group (P < 0.05). In conclusion, RJ supplementation improved performance parameters and unsaturated fatty acid ratios in the examined quail tissues.
Keywords: Quail; stocking density; performance; fatty acids; royal jelly